International region as a brand origin: Conceptualization and review - Chlivickas, Eugenijus; Smaliukienė, Rasa (Journal of Business Economics and Management, 2009)
The purpose of the paper is to examine the international region‐relation as a brand origin. The results of the theoretical analysis of this study provide a foundation for making suggestions about theoretical relationships between components of the brand origin. According to proposed theoretical model, communication with the consumers spreading from the strong business clusters in the international region creates emotional attitudes towards a brand origin; in addition, the quality of the products of the same clusters creates cognitive attitudes towards a brand origin. Our interest centred on a specific international area ‐ the Baltic Sea region. This region embodies the principles of shared values and common purpose, hence portrays a promising situation for regional branding. Performed empirical research allowed the analysis of both emotional and cognitive components of the brand origin. Therefore, the direct effects of the attributes of local brands on the brand origin were tested on the basis of telecoms and food industries in the Baltic Sea region. First Publish Online: 09 Jun 2011